Decarbonization Measure: A Concept towards the Acceleration of the Automotive Plant Decarbonization - Sami Alexandre Succar; Daniel Brissaud; Damien Evrard; Dominik Flick; Damien De la Fontaine (Systems, 2023)
Smart manufacturing systems enable simultaneous addressing of productivity, sustainability, and social improvements. The implementation of such systems in industries such as the automotive industry represents a promising way to meet stakeholders’ requirements concerning the decarbonization of their productive activities. In fact, this task is truly challenging for the automotive industry considering their complex organizational issues, generating knowledge sharing problems, and the diversity of plants’ context and characteristics. These facts make any decarbonization solution local, instead of being spread to a maximum of production units to potentially enhance decarbonization time efficiency. This article tackles these issues by providing a new organizational concept dealing with the relationships between decarbonization actors (energy managers and consultants) supported by the technical design of an IT knowledge management tool. These contributions will be based on the concept of decarbonization measure (DM) and illustrated by the case of Stellantis, one of the world leaders in terms of vehicle production, which develops a new organizational structure from local energy managers to corporate energy consultants.